A behavioural reasoning perspective on the consumption of local food. A study on REKO, a social media-based local food distribution system. (October 2021) - Kumar, Sushant; Talwar, Shalini; Murphy, Mikko; Kaur, Puneet; Dhir, Amandeep
Highlights: Behavioural reasoning theory (BRT) is used to explain attitude and brand love for local food. Self-identity is positively associated with reasons for, against and attitude towards local food. Supporting the environment, intrinsic quality, product attributes and price are associated with attitude and brand love. Positive attitude shapes brand love for local food. The mediating role of reasoning and attitude towards local food is confirmed. Abstract: Consumption of local food is increasing due to its convenience and multiple perceived benefits. However, the factors shaping consumer attitude towards local food and brand love for local food have received limited academic attention. The study thus investigates the under-explored concept of self-identity, attitude towards local food, and brand love, along with contextual variables with respect to local food consumption. Behavioural Reasoning Theory (BRT) is adopted as the theoretical frame in which self-identity is utilised as value, supporting the environment and positive product perception about the food sold by REKO are the reasons for choosing local food, and negative product perception about the food sold by REKO and price are reasons against selecting local food from REKO. Data from 2045 Finnish consumers of local food were collected and analysed, with the findings indicating that self-identity is associated with attitude towards local food, and reasons for as well as against the consumption of local food distributed by REKO. Moreover, reasons for, as measured through supporting the environment and positive product perception, and reasons against, as measured by negative product perception, are associated with attitude towards local food. However, along with reasons for, only price, representing reasons against, is associated with brand love, which, in turn, is associated with attitude towards local food. Reasons and attitude towards local food also have a mediation effect on the hypothesised associations. The findings contribute to improved theoretical insights on BRT, brand love, and local food distribution systems and offer useful managerial recommendations to help promote local food consumption and their underlying distribution systems.